2019
DOI: 10.1016/j.eats.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Medial Collateral Ligament Reattachment During High Tibial Osteotomy: Regulate Tension, Preserve Stability!

Abstract: High tibial osteotomy (HTO) is a commonly performed surgical procedure. Although it is well-known that the superficial medial collateral ligament (sMCL) should be released during HTO, there is still no agreement on performing its reattachment. Considering the function of the sMCL, after its release during HTO, increased medial joint instability may be expected. We present a technique for sMCL reattachment that prevents medial gapping development and maintains nearly native pressure on the medial compartment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…36 The American Journal of Sports Medicine 2022;50 (1):142-151 DOI: 10.1177/03635465211059162 Ó 2021 The Author(s) Some have even argued that the sMCL should be fixed after release. 30 Conversely, valgus laxity has not been cited as a common complication of HTO from a clinical perspective. 41 However, evidence supporting the safety of transection of the sMCL is still scarce and debatable.…”
mentioning
confidence: 99%
“…36 The American Journal of Sports Medicine 2022;50 (1):142-151 DOI: 10.1177/03635465211059162 Ó 2021 The Author(s) Some have even argued that the sMCL should be fixed after release. 30 Conversely, valgus laxity has not been cited as a common complication of HTO from a clinical perspective. 41 However, evidence supporting the safety of transection of the sMCL is still scarce and debatable.…”
mentioning
confidence: 99%
“…Some authors reported that sMCL should be kept to a minimum or fixed after manipulation to preserve stability [11][12][13]. Pape et al [13] reported an increased medial joint opening after release of the sMCL and possible late valgus instability.…”
Section: Discussionmentioning
confidence: 99%
“…While both techniques are widely performed by surgeons during MOWHTO, concerns have been raised about valgus laxity following sMCL release based on previous biomechanical studies and attempts to restore the sMCL after the release are being made [11][12][13][14]. However, some authors have reported that neither release nor transection increases valgus instability [7,15].…”
Section: Introductionmentioning
confidence: 99%
“…5 There has been much discussion about the management of the medial collateral ligament (MCL) following OW-HTO. 6,7 It is well-known that the MCL has to be released in OW-HTO. 6 In a standard approach for OW-HTO, the MCL is raised subperiosteally to the posteromedial tibia before a large retractor is placed behind the tibia to protect the neurovascular structures (NVS).…”
mentioning
confidence: 99%
“…6,7 It is well-known that the MCL has to be released in OW-HTO. 6 In a standard approach for OW-HTO, the MCL is raised subperiosteally to the posteromedial tibia before a large retractor is placed behind the tibia to protect the neurovascular structures (NVS). However, the surgical assistant often has to fight against the resistance of the intact MCL, and this poses challenges in visualization and instrument placement in the surgical field.…”
mentioning
confidence: 99%